MENJADI ISLAM SAMA DENGAN MENJADI MISKIN (Studi Adaptasi Muallaf Tionghoa Terhadap Masyarakat Aceh) - Triyanto Triyanto (Jurnal Community, 2016)
Muallaf life of Chinese Crossbreed community in Aceh Barat is not as good as with other crossbreed. Muallaf were expelled from their family, even business relationships between the members of the ethnic Chinese crossbreed also cut off so economically bankrupt and ended up living in poverty. Because of this, part of other ethnic Chinese who wants to convert to Islam with fear and cancel his intention. The emergence of the phrase "to be Islam is synonymous with being poor" because of poverty muallaf occurred since left the business relationship that has been built, and also expelled from their family, so that the financial assistance from the family when someone needs also suspended. One thing that makes business relations and expulsion of muallaf family leave because they have left ("betray") and their ethnic ancestry. Meanwhile, in the face of poverty, some of them were forced to leave Meulaboh city and live in Banda Aceh or Medan. It is not exactly known how the living conditions of ethnic Chinese crossbreed muallaf of Meulaboh in those cities. While others choose to stay in Meulaboh and live in simple life. To finance his family life, muallaf are working as parking attendants, bookselling, garbage collectors and scavengers, caring for and maintaining the child, as well as working as a factory worker. However, the simple and poor life would be rewarded with good, because it reverts Chinese crossbreed people can live together with Acehnese people. In the belief that a new life as a new muallaf will receive a trial from God. For that, there is only one strong determination to survive as a muallaf despite poor living up to his death, and the Lord called him in eternity. Keywords: adaptation, poverty, convert, Chinese, Meulaboh, Peranakan.